CURCUMIN AND WHEY PROTEIN BINDING AND STRUCTURAL CHARACTERISTICS OF THEIR COMPLEX EVIDENCED BY ATOMIC FORCE MICROSCOPY - RACZ, Levente Zsolt; RACZ, Csaba-Pal; MOCANU, Aurora; LEVEI, Erika; ARGHIR, George; POP, Lucian Cristian; TOMOAIA, Gheorghe; PETEAN, Ioan; PALTINEAN, Gertrud-Alexandra; TOMOAIA-COTISEL, Maria (Studia Universitatis Babeș-Bolyai Chemia, 2022)
Curcumin (CCM) has beneficial effects on human health due to its pharmacological activities, which have a protective role against many diseases. Whey protein concentrate (WPC) is a product from the milk industry that is often used to improve and stabilize different foods. It helps curcumin improve its water solubility, poor bioavailability, low stability, and efficacy. Atomic force microscopy (AFM) was employed to highlight the surface topography of adsorbed films of pure curcumin, pure whey protein concentrate, and their CCM-WPC complex. The obtained results show that individual nanoparticles, NPs, were mobilized into the aqueous dispersion and successfully adsorbed onto the glass slides as thin films. Their NPs shape is rounded, and their diameter differs on each sample, namely about 30 nm for CCM, around 55 nm for WPC, and about 40 nm for the CCM-WPC complex. It proves that both CCM and WPC molecules generate a complex that embeds them in a compact structure. The surface roughness was also monitored, and pure CCM produces the smoothest and uniform film, meanwhile, the presence of WPC makes several pores in the film surface which increases the roughness value. The obtained results provide useful evidence for the application of whey protein as an effective carrier of curcumin, a bioactive polyphenol compound. In addition, this work supports the application of the CCM-WPC complex as health supplements.